2016
DOI: 10.1149/07514.0301ecst
|View full text |Cite
|
Sign up to set email alerts
|

Ultralow Degradation Rates in HT-PEM Fuel Cells

Abstract: One of the major advantages of polybenzimidazole (PBI) based high temperature polymer electrolyte (HT-PEM) fuel cells compared to the low temperature representatives of this type of fuel cell technology is the higher tolerance against impurities like CO. Nevertheless lifetime and durability are still an issue. In this work, an improvement in degradation rates and therefore an extension of lifetime of HT-PEM fuel cells will be presented. Extended long term tests have been performed at different facilities under… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 8 publications
1
4
0
Order By: Relevance
“…The degradation rate of MEA B revealed a value of -6 µV/h and corresponds to both the performance and the voltage gap compared with the other three MEAs. This load cycling degradation rate is in the same range like the best published degradation rates for long term tests under constant load (1,3,4). MEA C shows the lowest performance and the highest degradation rate (-96 µV/h, see Table II) compared to the other MEAs shown in Figure 1, while the initial voltage is close to the starting value of MEA A.…”
Section: Resultssupporting
confidence: 74%
See 1 more Smart Citation
“…The degradation rate of MEA B revealed a value of -6 µV/h and corresponds to both the performance and the voltage gap compared with the other three MEAs. This load cycling degradation rate is in the same range like the best published degradation rates for long term tests under constant load (1,3,4). MEA C shows the lowest performance and the highest degradation rate (-96 µV/h, see Table II) compared to the other MEAs shown in Figure 1, while the initial voltage is close to the starting value of MEA A.…”
Section: Resultssupporting
confidence: 74%
“…Such features could be lifetime, performance and stability of the inserted materials. Typical scientific investigations representing also these quality issues are long term operation at constant load conditions (1)(2)(3)(4), start/stop-cycling (5)(6) and load cycling procedures (7). This paper focusses on accelerated stress tests to investigate PBI-based HT-PEM membrane electrode assemblies (MEA) from four different providers in order to provide a good overview on currently available MEAs.…”
Section: Introductionmentioning
confidence: 99%
“…The authors of this publication made similar observations with this type of MEA. A stable long term test showed degradation rates below 3 µV h −1 for 15,500 h. After this period, the MEA exhibited a large voltage drop and reached end of test (EoT) after 16,080 h; parts of this experiment have been published in .…”
Section: Introductionmentioning
confidence: 99%
“…In the past, it was used to analyse MEAs as well as bipolar plates in detail. These studies showed power losses due to MEA degradation in the form of membrane thinning or formation of pinholes, catalyst layer thinning and formation of cracks or even intrusion of GDL fibres (14)(15)(16). Carbon-based composite bipolar plates are prone to undergo corrosion and thus fail to ensure a proper functionality during critical conditions (17,18).…”
Section: Introductionmentioning
confidence: 99%